Planning and Designing the Lapindo Mudflow Museum in Sidoarjo - Nadhila, Nadia Nurarifah; Komara, Indra; Widjajanti, Wiwik Widyo; Laksmiyanti, Dian Pramita Eka (Faculty of Civil Engeneering and Planning - ITATS, 2024)
Disasters are situations due to natural factors (such as earthquakes, tsunamis, volcanic eruptions, flash floods, and droughts), non-natural factors, or human factors that disrupt human activities. They cause loss of life, loss of property, environmental destruction, and psychological distress. One significant natural disaster in Indonesia was the hot mudflow eruption in Porong, Sidoarjo, East Java, on May 29, 2006. The Lapindo Mudflow is an ongoing event with no signs of stopping. The choice to construct a Lapindo Mudflow Museum is due to the absence of such a museum, despite the significant impact of this disaster in Indonesia. The plan and design of the Lapindo Mudflow Museum in Sidoarjo applies the theme of metaphorical architecture because it is deemed appropriate for a museum building. Metaphorical architecture involves the creativity of architects in connecting objects, metaphors, or expressions to create forms that differ from their original shapes while retaining similarity. Buildings with metaphorical architectural designs have unique features that relate to the message intended by their creators. The Lapindo Mudflow will be built in Sidoarjo, specifically in Gelam Urban Village, Candi District. This museum will serve not only as a museum but also as a symbolic monument to the 2006 Lapindo Mudflow disaster and to commemorate its victims.